The Influence Of Green Brand Towards Consumers’ Green Purchase Intention: An Empirical Study Of Lokalate Medan - Erika, Erika; Alfonsius, Alfonsius (SEAN Institute, 2024)
In the era of intense industrial and production development, environmental issues become one of the most mentioned global community’s concerns. Many companies will take this opportunity to help improve their sustainability development by implementing a green marketing strategy. This research discusses the implementation of the green concept by implementing eco-friendly marketing to boost consumers’ purchase intention, also illustrates the important role of green brand and waste management. The purpose of this paper is to determine the causal relationship between variables. This study uses nonprobability sampling namely snowball sampling to target respondents that are Lokalate consumers with an age range of 18-45 years. Data as many as 140 respondents gathered by distributing questionnaires using Google Forms. All measurement items were measured on five point Linkert-type scales. Data analyzed using SPSS 25.0 with multiple linear regression (MLR) analysis. The results of this study indicate that green brand has a significant effect on green purchase intention. The four hypotheses in this paper have been tested. Green brand positioning significantly gives positive influence to green purchase intention. Green brand attitude significantly gives positive influence to green purchase intention and green brand knowledge significantly gives positive influence to green purchase intention. This research resulted in positive impact in the form of improving the economy of UMKM in Indonesia and allows reducing waste to meet the concern of green consumers.